Comparison of yield and chemical composition of essential oils from lemongrass (Cymbopogon Citratus) extracted with Microwave-Assisted Hydrodistillation (MAHD) and Conventional Hydrodistillation (HD) methods / Ranitha. M....[et al.] - M., Ranitha.; H.N, Abdurahman; A.S, Ziad; H.N, Azhari; S, Thana Raj (2014)
The demand of essential oil in current industry has increased due to its bioactive compound that shows various therapeutic effects. Therefore, the qualities of essential oil mainly depend on its constituents. This study was carried out to determine the effects of Microwave-assisted hydrodistillation (MAHD) and hydrodistillation (HD) methods on yield, chemical composition and toxicity of essential oil from Lemongrass (Cymbopogon citratus). A pale yellow oil yield of 1.46 % (90 min) and 1.38% (180 min) were obtained from MAHD and HD methods, respectively. GC-MS results shows a total of twenty compounds in MAHD oil and seven compound in HD oil. MAHD oil contained slightly higher amount of citral, which is the key component of Lemongrass (Cymbopogon citratus), compared to HD oil, 86.48% and 83.15%, respectively. However, hydrodistilled oil showed the presence of higher β-Myrcene, 9.91%, and only 3.96% were found in the MAHD oil. Other identified constituents, include Linalool, 1,6-Octadiene,3,5-dimethyl-,trans, Pinane, Geranic acid and 1,5-Octadiene. A minor variation in the total chemical composition of essential oil may contribute for different level of biological activity expression.